The Relationship Between Etiquette and Quality of Service of School Administrative Staff with Student Satisfaction at State Vocational High Schools in Tuban Regency - Nuryani, Nuryani; Zulkarnain, Wildan; Sunandar, Asep; Imron, Ali (Proceedings Series of Educational Studies, 2024)
The objectives of this research are: (1) To analyze the service etiquette of school administrative staff at Vocational High Schools in Tuban Regency; (2) To analyze the quality of school administrative staff services based on the 3A concept (attitude, attention, action) at Vocational High Schools in Tuban Regency; (3) To analyze the satisfaction level of Vocational High Schools students in Tuban Regency; (4) To analyze the relationship between school administrative staff service etiquette and student satisfaction at Vocational High Schools in Tuban Regency; (5) To analyze the relationship between the quality of school administrative staff services and student satisfaction at Vocational High Schools in Tuban Regency; (6) To analyze the relationship between school administrative staff service etiquette and quality with student satisfaction at Vocational High Schools in Tuban Regency. This research uses a quantitative approach with a descriptive correlational type. The population in this study consists of Vocational High Schools students in Tuban Regency, with a total population of 11,490. The sample was selected using proportional random sampling and consisted of 400 students. Data collection was done using questionnaires. Data analysis used descriptive correlation analysis with Pearson product moment correlation, tested using IBM Statistics 22. The results of this research show: (1) The level of school administrative staff service etiquette falls within the good category; (2) The quality of school administrative staff services falls within the good category; (3) The level of student satisfaction falls within the good category; (4) There is a positive and significant relationship between school administrative staff service etiquette and student satisfaction at Vocational High Schools in Tuban Regency; (5) There is a positive and significant relationship between the quality of school administrative staff services and student satisfaction at Vocational High Schools in Tuban Regency; (6) There is a positive and significant relationship between school administrative staff service etiquette and quality with student satisfaction at Vocational High Schools in Tuban Regency. Keywords: etiquette; quality; students satisfaction